Menjaga Kesehatan Fisik dan Mental Lanjut Usia melalui Program Pemberdayaan Lansia Binaan Rumah Zakat Makassar - Kurniari Zainuddin; Citra Azzahra Ansar; Khaira Ummah Febrian A; Salsabila Qur’ana Putri S; Widya Alzipah Nur; Yulastri Yulastri (CV. Ulil Albab Corp, 2024)
Old age is a continuous process in the dimension of time and is the final phase of a person's development. The aging process that occurs in the elderly will cause several health problems in the elderly. These emerging health problems are influenced by a decline in several aspects such as the physical, psychosocial and intellectual capacity of the elderly which are closely related to changes in cognitive function in the elderly. The research was conducted at the Ramah Lansia built by Rumah Zakat, Rappokalling District, Makassar, taking 50 elderly subjects who were recorded as elderly people. Ramah Aman Program includes counseling, cadre training, elderly posyandu, entrepreneurship education and elderly exercise. Judging from this program, the elderly assisted by Rumah Zakat Makassar only receive physical treatment but not the mental health of the elderly, even though we all know that physical health and mental health must be maintained considering that their age is very vulnerable to various kinds of diseases. The research uses a phenomenological approach to directly examine the in-depth experiences of the research subjects. There are various additional programs created as a form of community service that can help the elderly improve their mental health, providing a positive impact in improving the physical and mental health of the Elderly Cadres assisted by Rumah Zakat Makassar.